Glucose and Fat Metabolism in Narcolepsy and the Effect of Sodium Oxybate: A Hyperinsulinemic-Euglycemic Clamp Study - Donjacour, Claire E. H. M. (Associated Professional Sleep Societies, LLC, 2014)
INTRODUCTION: Narcolepsy is associated with obesity though it is uncertain whether this is caused by changes in glucose and fat metabolism. Therefore, we performed a detailed analysis of systemic energy homeostasis in narcolepsy patients, and additionally, investigated whether it was affected by three months of sodium oxybate (SXB) treatment. METHODS: Nine hypocretin deficient patients with narcolepsy-cataplexy, and nine healthy sex, age, and BMI matched controls were enrolled. A hyperinsulinemic-euglycemic clamp combined with stable isotopes ([6,6-(2)H(2)]-glucose and [(2)H(5)]- glycerol) was performed at baseline. In seven patients a second study was performed after three months of SXB treatment. RESULTS: Glucose disposal rate (GDR) per unit serum insulin was significantly higher in narcolepsy patients compared to matched controls (1.6 ± 0.2 vs. 1.1 ± 0.3 μmol/kgFFM/min/mU×L; P = 0.024), whereas β-cell function was similar (P = 0.50). Basal steady state glycerol appearance rate tended to be lower in narcolepsy patients (5.2 ± 0.4 vs. 7.5 ± 1.3 μmol/kg(FM)/min; P = 0.058), suggesting a lower rate of lipolysis. SXB treatment induced a trend in reduction of the GDR (1.4 ± 0.1 vs. 1.1 ± 0.2 μmol/kgFFM/min/mU×L; P = 0.063) and a reduction in endogenous glucose production (0.24 ± 0.03 vs. 0.16 ± 0.03 μmol/kgFFM/min/mU×L: P = 0.028) per unit serum insulin. After SXB treatment lipolysis increased (4.9 ± 0.4 vs. 6.5 ± 0.6 μmol/kg(FM)/min; P = 0.018), and body weight decreased in narcolepsy patients (99.2 ± 6.0 vs. 94.0 ± 5.4 kg; P = 0.044). CONCLUSION: We show that narcolepsy patients are more insulin sensitive and may have a lower rate of lipolysis than matched controls. SXB stimulated lipolysis in narcolepsy patients, possibly accounting for the weight loss after treatment. While sodium oxybate tended to decrease systemic insulin sensitivity, it increased hepatic insulin sensitivity, suggesting tissue-specific effects. CITATION: Donjacour CE; Aziz NA; Overeem S; Kalsbeek A; Pijl H; Lammers GJ. Glucose and fat metabolism in narcolepsy and the effect of sodium oxybate: a hyperinsulinemic-euglycemic clamp study. SLEEP 2014;37(4):795-801.